PENGARUH PRODUK, PROMOSI DAN KINERJA KARYAWAN TERHADAP KEPUASAN KONSUMEN PT. PRUDENTIAL LIFE INSURANCE - Katherine Katherine; Calen Calen; Hendry Dunan (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This research aims to determine the effect of product, promotion and employee performance on customer satisfaction at PT. Prudential Life Insurance (Bank UOB IR.H Juanda Medan Branch). The research data was obtained from the results of questionnaires with related parties according to the research objectives. This research approach uses quantitative methods because the aim of this research is to explain and test hypotheses regarding the influence of predetermined variables with a total of 87 respondents who actively purchase insurance which is used as a data collection tool in the questionnaire. From the results of research using the SPSS program, it shows that the product has a positive and significant effect on consumer satisfaction. This shows the value of tcount (9.306) > ttable (1.987) with a significance value of (0.000 < 0.05), meaning that there is a positive and significant effect of the product on performance. Employees, Promotion research results also using the SPSS program show that Promotion has a positive and significant effect on consumer satisfaction. This shows the value of tcount (2.234) > ttable (1.987) with a significance value of (0.028 < 0.05) meaning there is a positive and significant influence products on employee performance, and the results of employee performance research also using the SPSS program show that employee performance has a positive and significant influence on consumer satisfaction. This shows the value of tcount (2.790) > ttable (1.987) with a significance value of (0.007<0.05) meaning there is product positive and significant influence on employee performance. Based on the research conducted, it can be concluded that Products, Promotions and Employee Performance have a positive and significant influence on customer satisfaction at PT. Prudential Life Insurance (Bank UOB IR.H Juanda Medan Branch). Keywords: Product, Promotion, Employee Performance, Consumer Satisfaction